2021
DOI: 10.2147/dmso.s298950
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Regulates MALAT1/miR-200c/NRF2 Activity to Protect Against Podocyte Pyroptosis Induced by High Glucose

Abstract: Background Diabetic nephropathy (DN) is one of the main complications of diabetes mellitus (DM), which leads to the long-term loss of kidney functions. Long noncoding RNAs (LncRNAs) can alleviate DN by interacting with microRNAs (miRNAs). In this work, we aimed to explore the effects of the MALAT1/miR-200c/NRF2 regulatory axis on the pyroptosis and oxidative stress (Oxidative stress, OS) of renal podocytes in high glucose (HG) environment and whether the lipid-lowering drug atorvastatin (AT) can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…lncRNA regulates the progression of cells in a variety of ways which includes oxidative stress and autophagy. In diabetic nephropathy, MALAT1 regulated oxidative stress to promote the injury of podocyte cell via the miR-200c/NRF2 axis [48]. Knockdown of MALAT1 activated cell autophagy and inhibited the progression of atherosclerosis…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA regulates the progression of cells in a variety of ways which includes oxidative stress and autophagy. In diabetic nephropathy, MALAT1 regulated oxidative stress to promote the injury of podocyte cell via the miR-200c/NRF2 axis [48]. Knockdown of MALAT1 activated cell autophagy and inhibited the progression of atherosclerosis…”
Section: Discussionmentioning
confidence: 99%
“…Hence, MALAT1 may also generate oxidative stress in diabetic renal tissues by regulating KLF5/ NOX4 signaling. Additionally, it has been demonstrated that the expression levels of Nrf2 and HO-1 are both elevated in mouse podocyte MPC-5 cells with MALAT1-3 siRNA under high glucose conditions [22]. As mentioned above, Nrf2 is a redox-sensitive transcription factor, which regulates the expression of various antioxidant enzymes via ARE [23].…”
Section: Malat1mentioning
confidence: 93%
“…miR-200c overexpression can promote OS in endothelial cells and interact with MALAT1 structurally ( Li et al, 2016 ; Carlomosti et al, 2017 ). In addition, Zuo Y et al demonstrated that AT suppresses caspase-1, GSDMD, and NLRP3 expressions by regulating MALAT1/miR-200c/NRF2 activation to prevent podocyte pyrolysis and OS induced by high glucose ( Zuo et al, 2021 ). It opens a new door to AT-induced therapy for diabetes complications.…”
Section: Regulation Of Lncrna On Nlrp3 Inflammation In Diabetes and Its Complicationsmentioning
confidence: 99%